2021
DOI: 10.3390/jpm11050429
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Rehabilitation in Parkinson’s Disease: A Systematic Review and Meta-Analysis

Abstract: Cognitive deficits influence the quality of life of Parkinson’s disease (PD) patients. In order to reduce the impact of cognitive impairment in PD, cognitive rehabilitation programs have been developed. This study presents a systematic review and meta-analysis regarding the effectiveness of cognitive rehabilitation in non-demented PD patients. Twelve articles were selected according to PRISMA guidelines. The systematic review showed that attention, working memory, verbal memory, executive functions and process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Second, previous studies have suggested that cognitive levels of jobs correlate with better processing speed and that processing speed is one of the most frequently improved domains by cognitive rehabilitation in PD. 46,47 Therefore, although the PASE questionnaire quantifies only the working hours per week but not the cognitive levels of each job, we speculate that work-related cognitive tasks may be behind the observed association between work-related activities and slower decline in processing speed. Finally, the observed association between household activities and slower decline in ADL might possibly suggest that becoming familiar with household chores is important for maintaining high ADL over time.…”
Section: Discussionmentioning
confidence: 91%
“…Second, previous studies have suggested that cognitive levels of jobs correlate with better processing speed and that processing speed is one of the most frequently improved domains by cognitive rehabilitation in PD. 46,47 Therefore, although the PASE questionnaire quantifies only the working hours per week but not the cognitive levels of each job, we speculate that work-related cognitive tasks may be behind the observed association between work-related activities and slower decline in processing speed. Finally, the observed association between household activities and slower decline in ADL might possibly suggest that becoming familiar with household chores is important for maintaining high ADL over time.…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, the improvements were not maintained after six months. These recent studies show positive but modest results as measured by 'laboratory' neuropsychological tests, as opposed to the self-measure of executive functioning, evaluating daily functioning, used in the present study [50][51][52].…”
Section: Plos Onementioning
confidence: 43%
“…Considering that PD is a physically and psychologically debilitating disorder, health care professionals should adopt a holistic approach to PD rehabilitation [ 65 ]. Treatment objectives vary among individuals, highlighting the need for personalized intervention; so, a variety of non-pharmacological therapies should also be taken into account [ 66 ], such as, mindfulness yoga [ 65 ], psychological interventions [ 67 ], spiritual resilience [ 68 ], physical therapy [ 69 ], cognitive training [ 70 ], and speech therapies [ 71 ]. These therapies could be included in the clinical manage of PD patients.…”
Section: Discussionmentioning
confidence: 99%